Kitsan O. V. Folk borrowings and a syllabic element of rhythmomelodics of V. Holoborodko - Kitsan O. V. (Philological Treatises, 2020)
The article focuses on syllabic rhythmomelodics in the works of a famous poet and the link of his works with folklore.